SSCM Performance Improvement Strategy of Container Shipping Industry in Indonesia - Gena Bijaksana; Arief Daryanto; Tridoyo Kusumastanto; Nimmi Zulbainarni (School of Business, IPB University (SB-IPB), 2018)
The objectives of this study are to measure and analyze the factors that significantly impact the performance of Sustainable Supply Chain Management (SSCM) container shipping industry in Indonesia. This research will then formulate recommendations on SSCM performance improvement strategy using SEM-PLS method. The results show that currently the business actor and service user perceive the SSCM performance of container shipping industry in Indonesia as low. Furthermore, four latent variables give significant and positive impact to SSCM performance. The latent variables include Technology, Integrated Logistic System, Sustainable Market Orientation and Fair-Trade System. The Technology and Integrated Logistic System as the priority should be give more attention. The conclusion of the research result shows that strategy to improve the SSCM performance of container shipping industry in Indonesia must be carried out through a holistic approach and seen as a system. The managerial implication of this study is that the four latent variables of the model sorted, according to their priorities from the total effect coefficients, can be applied as a strategy to improve SSCM performance.Keywords: sustainable supply chain, container shipping, SEM, SSCM